The Role of Public Relations at SMKN 3 Depok in Preparing Graduates Ready to Work in the World of Industry - Rajagukguk, Djudjur Luciana; Lestari , Karin Septia Dwi (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This research aims to find out about the role of school public relations in preparing students to enter the industrial world. Of course, the role of Vocational High Schools cannot be underestimated, there is no longer the position of Vocational Schools as reserve schools which are the second choice, if you cannot enter the desired high school. This research uses descriptive qualitative methods with a constructivism paradigm. This research collects data through interviews, observation and documentation and data analysis by reducing data, presenting data and drawing conclusions. Talking about the role of public relations means discussing an industry or institution that communicates with the public or society. Two-way communication is established with the public to provide support for management functions and objectives by increasing the development of cooperation and fulfilling common interests. So the role of public relations will be seen as an Expert Preciber (management expert or advisor). Public relations practitioners are considered as experts who can provide solutions to the public relations problems of an organization and management. Communication Facilitator means that public relations practitioners act as intermediaries, liaisons, translators and mediators, and ensure the realization of two-way communication between the organization and its public, Problem Solving Process Facilitator means that public relations is involved in solving organizational problems even though its role is still in the communication corridor.